2016
DOI: 10.1002/2015gl067298
|View full text |Cite
|
Sign up to set email alerts
|

Viscous flow rates of icy topography on the north polar layered deposits of Mars

Abstract: We investigate the importance of viscous flow in shaping topography at the north polar layered deposits (NPLD) of Mars by using finite element modeling to calculate the distribution of stresses and flow velocities. Present‐day impact craters on the NPLD are too small and cold for viscous relaxation to have been an important mechanism in controlling their current dimensions; this effect may be ignored when analyzing crater size‐frequency distributions. Scarps at the NPLD margins, where avalanches of dust and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 63 publications
(101 reference statements)
0
26
0
Order By: Relevance
“…This calculation results in a negative exponent for the crater lifetime, indicating that a 31 m diameter crater (the smallest crater size considered in the statistically complete range) would be preserved longer than a ~200 m diameter crater. There is no physical mechanism that removes larger craters faster than smaller craters, except for viscous relaxation and that has been found to be negligible here [ Sori et al , ]. The errors on this solution permit a value of zero, and we interpret the actual value to be close to it.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This calculation results in a negative exponent for the crater lifetime, indicating that a 31 m diameter crater (the smallest crater size considered in the statistically complete range) would be preserved longer than a ~200 m diameter crater. There is no physical mechanism that removes larger craters faster than smaller craters, except for viscous relaxation and that has been found to be negligible here [ Sori et al , ]. The errors on this solution permit a value of zero, and we interpret the actual value to be close to it.…”
Section: Resultsmentioning
confidence: 99%
“…Larger craters (≳1 km diameter) on the South Polar Layered Deposits are affected by viscous relaxation [ Pathare et al , ]. However, a recent study of flow of icy topography of the NPLD using finite element models found that viscous relaxation has been negligible in shaping the topography of presently observed NPLD impact craters [ Sori et al , ]. Therefore, changes in depth are dominated by other factors, like crater infilling.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of geological processes and structures can contribute to geothermal heat flow (e.g., Rezvanbehbahani et al, 2017). This effect is not observed to be occurring in the polar layered deposits (Karlsson et al, 2011), nor is it predicted to occur except possibly at some margins (Sori et al, 2016). Models of Martian midlatitude glaciation similarly found that increases in geothermal heat flux were needed to achieve subglacial melting but also required strain heating of the ice due to internal deformation of flowing ice (Butcher et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of laboratory data, the effect of particulates has been parameterized by multiplying the effective viscosity by a factor of e bnφp , where b = 2 is experimentally determined 13,21,40,41 . By this formulation a particulate fraction of ϕ p = 0.5 for grain-boundary sliding (n = 1.8) results in an approximately factor of six increase in viscosity.…”
Section: Methodsmentioning
confidence: 99%